Static mechanical, thermal stability, and interfacial properties of superheated steam treated oil palm biomass reinforced polypropylene biocomposite - Mohd Warid, Muhammad Nazmir; Tengku Yasim Anuar, Tengku Arisyah; Ariffin, Hidayah; Hassan, Mohd Ali; Andou, Yoshito; Shirai, Yoshihito (Universiti Putra Malaysia Press, 2020)
In this study, three types of oil palm biomass (OPB) namely, oil palm mesocarp fiber (OPMF), oil palm empty fruit bunch (OPEFB) and oil palm frond (OPF), were studied and compared as the alternative fillers in the biocomposite reinforced polypropylene (PP). The fibers were treated using the optimal condition of superheated steam treatment obtained from previous study. The OPB/PP biocomposites at weight ratio of 30:70 were fabricated by melt blending technique and hot pressed moulding. Results showed that the tensile and flexural properties of optimized-SHS-treated OPB/PP biocomposites were improved by 9 – 30% and 9 – 12%, respectively compared to the untreated OPB/PP biocomposites. The same observation was recorded for thermal stability. Improved surface morphology as shown by the tensile fracture surface indicates better interfacial adhesion between SHStreated OPB fibers with PP matrix during blending. Overall results showed that OPF/ PP biocomposites had better properties compared to biocomposites prepared from OPMF and OPEFB, suggesting that OPF is a better OPB fiber choice as a filler in PP reinforced biocomposite.